Investing in children: The impact of EU tax and benefit systems on child poverty and inequality - Kateryna Bornukova; Adrian Hernández; Fidel Picos (European Commission, Joint Research Centre (JRC), 2024)
The EU committed to meet the poverty reduction target set in the European Pillar of Social Rights Action Plan, which entails to reduce the number of children at risk of poverty or social exclusion by 5 million by 2030. The paper assesses the impact of child-contingent cash support in EU-27 in 2019-2022 on child poverty and inequality and sheds light on the role this kind of support plays, or could further play, when it comes to meeting the 2030 child poverty target. We use the microsimulation model EUROMOD to identify child-contingent cash support and find significant variation in average support per child across EU-27, ranging from 3.2% of GDP per capita in Ireland to 12% of GDP per capita in Austria. Correspondingly, the impact of child-contingent cash support on reducing child at-risk-of-poverty rates varies from 4 p.p. in Portugal to 16 p.p. in Slovakia. The inequality-reducing effect is highly correlated with poverty reduction. With rare exceptions, countries rely on child benefits as a primary source of child-contingent cash support, as opposed to tax-based support. Non-poor households receive over 50% of total child-contingent cash support in most EU countries. Means-tested benefits, while better targeted to impoverished households, do not always provide enough support to lift them above the poverty line. We do not observe correlation between child-contingent cash support, other benefits, and in-kind child support.
Keywords: 330